2013
DOI: 10.2133/dmpk.dmpk-13-rg-017
|View full text |Cite
|
Sign up to set email alerts
|

Variability of Bioavailability and Intestinal Absorption Characteristics of Bisoprolol

Abstract: We previously reported that renal function is partly responsible for the interindividual variability of the pharmacokinetics of bisoprolol. The aim of the present study was to examine the variability of bioavailability (F) of bisoprolol in routinely treated Japanese patients and intestinal absorption characteristics of the drug. We first analyzed the plasma concentration data of bisoprolol in 52 Japanese patients using a nonlinear mixed effects model. We also investigated the cellular uptake of bisoprolol usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 16 publications
1
8
0
Order By: Relevance
“…On the other hand, the uptake of quinidine was decreased by Acute-NH4Cl treatment, which induces the alkalization of intracellular pH (Fig 1A). 4,5) The pro le of intracellular pH-dependent uptake of quinidine into HT-29 cells was also consistent with that in Caco-2 and LS180 cells (Fig 1). These ndings suggested that the H + antiporter(s) in HT-29 cells may be similar/identical to that (those) in Caco-2 and LS180 cells.…”
Section: Uptake Of Quinidine In Caco-2 Ls180 and Ht-29 Cellssupporting
confidence: 84%
See 2 more Smart Citations
“…On the other hand, the uptake of quinidine was decreased by Acute-NH4Cl treatment, which induces the alkalization of intracellular pH (Fig 1A). 4,5) The pro le of intracellular pH-dependent uptake of quinidine into HT-29 cells was also consistent with that in Caco-2 and LS180 cells (Fig 1). These ndings suggested that the H + antiporter(s) in HT-29 cells may be similar/identical to that (those) in Caco-2 and LS180 cells.…”
Section: Uptake Of Quinidine In Caco-2 Ls180 and Ht-29 Cellssupporting
confidence: 84%
“…In addition, the uptake of quinidine into Caco-2, LS180, and HT-29 cells was significantly inhibited by diphenhydramine (Fig 1). Furthermore, Pre-NH4Cl treatment, which induces the acidification of intracellular pH, 4,5) increased the uptake of quinidine into HT-29 cells (Fig 1A). On the other hand, the uptake of quinidine was decreased by Acute-NH4Cl treatment, which induces the alkalization of intracellular pH (Fig 1A).…”
Section: Uptake Of Quinidine In Caco-2 Ls180 and Ht-29 Cellsmentioning
confidence: 92%
See 1 more Smart Citation
“…Our previous study suggested that the rate/extent of the intestinal absorption of bisoprolol is one of the causes of the interindividual variability of the pharmacokinetics of the drug [14]. In addition, the cellular uptake of bisoprolol into intestinal epithelial cells is plausibly mediated by the postulated H + /tertiary amine antiporter [14]. In the present study, the cellular uptake of flecainide in LS180 cells was significantly decreased by acidification of the extracellular medium, and was inhibited by tertiary amines, such as diphenhydramine and quinidine (Figure 4, Table 3).…”
Section: Discussionmentioning
confidence: 99%
“…To evaluate the cellular uptake of flecainide, the LS180 cells were seeded on plastic dishes of a multiwell plate as described previously . The composition of the incubation medium was as follows: 125 m m NaCl, 4.8 m m KCl, 5.6 m m d ‐glucose, 1.2 m m CaCl 2 , 1.2 m m KH 2 PO 4 , 1.2 m m MgSO 4 · 7H 2 O and 25 m m 2‐[4‐(2‐hydroxyethyl)‐1‐piperazyl]ethanesulfonic acid (HEPES) (pH 6.4 or 7.4).…”
Section: Methodsmentioning
confidence: 99%